Management of Complicated Appendicitis in Al-Thawra Modern General Hospital Sana’a -Yemen from November 2019 to November 2020 - Obadiel, Yasser Abdurabu; Morshed, Ibrahim Dahan Hussein (Journal of medical and pharmaceutical sciences, 2021)
Background: Complicated appendicitis causes morbidity and mortality more than simple appendicitis. Complicated appendicitis includes appendicular mass, appendicular abscess, perforated appendicitis. Objective: To study presentation of complicated appendicitis regarding to age, sex and complain duration, also to study management of complicated appendicitis and his response to conservative management. Methods: A prospective, observational study was conducted in the department of general surgery at AL-Thawra hospital during the period from Nov 2019 to Nov2020. The data was collected using clinical examination and follow up, and was analyzed using SPSS 24. Results: A total of 57 patients diagnosed as complicated appendicitis, aged from 6 to 60 years were admitted, mean age was 28 years. Male to female ratio was 1.6:1. The complaint duration was more than 3 days in 34 cases (59%), total leucocytes count was >18 × 103 in 28 cases (49.1%). Twenty patients (35.1%) diagnosed as generalized peritonitis, 18 cases (31.6%) diagnosed as localized peritonitis, 14 patients (24.6%) diagnosed as appendicular mass, and 5 cases (8.8%) diagnosed as appendicular abscess. Forty cases (70.2%) underwent surgical intervention, whereas 17 cases (29.8%) improved with conservative management. Fifteen cases (37.5%) of operated patients underwent simple appendectomy and 13 cases (32.5%) underwent appendectomy with drain, and 12 cases (30%) underwent midline laparotomy. Most appendicular mass cases 12 (85.7%) were managed conservatively and 2 cases (14.3%) were operated. Three cases (60%) of appendicular abscess were aspirated, 2 cases (40%) were drained. Surgical site infection was 27.5% of operated cases. Conclusions: Complicated appendicitis can be suspected through clinical presentation, duration of complains and inflammatory response. Management of complicated appendicitis varies accordingly from conservative conventional to midline laparotomy.